Structural Analysis of the Effect of Women's Personality Traits on Their Entrepreneurship with a Moderating Role of Educational Level in Khuzestan Province - Sara Mohammadi; Farajallah Rahimi; Mahdi Nadaf; Touran Argha (توسعه اجتماعی)
Women's entrepreneurship, in addition to helping the economic development of a country can also lead to further growth and prosperity of this huge segment of society. So, this study aims to investigate the personality traits affecting women's entrepreneurship with respect to the moderating role of education level. The research method is applied in terms of purpose and descriptive-correlation in terms of data collection. The statistical population of the study is 344 girls and women entrepreneurs of Khuzestan province who were selected by non-random sampling available method. Data were collected using the Entrepreneurial Personality Traits Questionnaire of Kordnaeij & et. al., (2007) and McKerry and Custa (2004), and the Zamptakis and Mustakis (2007), Entrepreneurial Behavior Questionnaire and data analysis was performed using structural equation modeling and smart-PLS3 software. According to the research findings, the characteristics of responsibility (=β 0.18(, risk-taking (=β 0.10(, need for achievement (=β 0.14(, challenging works & goals (=β 0.08(, open-mindedness (=β 0.12(, extraversion (=β 0.12(, and kinship (=β 0.16( have a positive and significant effect on women's entrepreneurship. Among these personality traits, responsibility and kinship had the most impact, and challenging and risk-taking had the least impact on women entrepreneurs. The results also showed that the level of education moderates the effect of risk-taking, success, challenging and open-mindedness on entrepreneurship, but does not have a moderating effect on the characteristics of responsibility, extraversion and kinship. The results show that women's entrepreneurship is significantly affected by their individual and personality characteristics. Women's education level can also enhance this impact.